Evangelienbuch. - Otfrid, von Weissenburg, active 9th century (Evangelienbuch, 2010)
The Heidelberg Manuscript P of Otfrid's Evangelienbuch also leads us close to the author. It was written at the end of the 9th century by two of Otfrid's pupils, who had already been involved with V (Cod. Vindobonensis 2687) (Vol. I,1 and I,2) and is characterised by artistic illuminated capitals, display scripts, neumata and historically significant linguistic variants. Manuscript D ("Discissus" Fulda around 975), of which only fragments have been preserved, completes the diplomatic edition of Otfrid texts VPD.